THE EFFECT OF NITROGLYCERIN ON RADIAL ARTERY OCCLUSION AFTER TRANSRADIAL CATHETERIZATION : A SYSTEMATIC REVIEW - Padmi Suwari Cokorda Istri (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Background : Transradial access is preferred approach for coronary angiography andÂ PCI. Although, access site-related complications can occur following transradial access. RAO is the most common postprocedural complication. It has been reported that nitroglycerin can dilate radial artery in patients undergoing transradial coronary catheterization without affecting blood pressure. Objective: This study aimed to evaluate the effect of nitroglycerin on RAO after transradial catheterization. Methods : We searched RCT from Cochrane, PubMed, Science Direct, NCBI, and BMJ. Titles, abstracts, and full texts were screened using inclusion criteria to filter out irrelevant studies. Quality assessment were undertaken using Jadad scale and the results have been presented as a narrative overview with figures. Results : Three studies were included after screening 206 records. Two studies demonstrated statistically significant results that giving nitroglycerin reduced the risk of RAO after transradial catheterization, compared with the comparator groups (p < 0.05). These studies were Chen Y et al 2018 (95% CI 0.116 - 0.998; p = 0.04) and Dharma S et al 2015 (OR : 0.62; 95% CI: 0.44 â€“ 0.87; p = 0.006). Conclusions : This study demonstrated benefit of using nitroglycerin for reducing incidence of RAO after transradial catheterization.